Curricular Influence and Perceptions of Engineering Graduates on Socio Ethical Issues Related to Biotechnology - Bhat, Savithri; Rajyalakshmi, M. (Journal of Engineering Education Transformations, 2015)
The impact of BT is on all strides of mankind, the fallout of which is the skepticism about social acceptance of BT products and processes.With appropriate subject knowledge the perception of an individual in this regard will undergo radical transformation. In view of this, ethical and safety issues related to BT are introduced as component of core courses in the curriculum of Biotechnology Engineering education. The present study involves survey pertaining to socio ethical aspects. The survey was conducted on biotechnology engineers, graduated over a period of seven years (2006 to 2012). The responses obtained indicated the ability of the graduates to judge a complex situation related to ethics in BT. Also, responses of the graduates displayed high level of social awareness and responsiveness.